2003
DOI: 10.1046/j.1532-5415.2003.51551.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Exercise on Physical Functioning and Falls in Frail Older People Living in Retirement Villages: A Randomized, Controlled Trial

Abstract: These findings show that group exercise can prevent falls and maintain physical functioning in frail older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
0
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(274 citation statements)
references
References 25 publications
10
243
0
16
Order By: Relevance
“…Our results are in agreement with a previous study that investigated the effects of multicomponent exercise interventions in the frail elderly. Lord et al (2003) found that 12 weeks of an intervention that included gait, balance, and weight-bearing exercises resulted in 22 % fewer falls in frail elderly individuals compared with control subjects. In addition, Binder et al (2002) showed significant improvements in balance and physical performance scores in the physically frail elderly after 36 weeks of multicomponent exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with a previous study that investigated the effects of multicomponent exercise interventions in the frail elderly. Lord et al (2003) found that 12 weeks of an intervention that included gait, balance, and weight-bearing exercises resulted in 22 % fewer falls in frail elderly individuals compared with control subjects. In addition, Binder et al (2002) showed significant improvements in balance and physical performance scores in the physically frail elderly after 36 weeks of multicomponent exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the physical domains that are related to frailty, physical activity is one of the most important components in the prevention and treatment of this syndrome. Indeed, the benefits of physical exercise in improving the functional capacity of frail older adults have been the focus of considerable recent research (Fiatarone et al 1994;Hauer et al 2001;Barnett et al 2003;Lord et al 2003;Serra-Rexach et al 2011;Villareal et al 2011;Clemson et al 2012;Freiberger et al 2012;Kim et al 2012). In a recent systematic review that investigated the effectiveness of different exercise interventions on the incidence of falls, gait ability, balance, and strength, 70 % of the studies included showed a reduction in the incidence of falls, 54 % showed enhancements of gait ability, 80 % showed improvements in balance, and 70 % reported increases in muscle strength .…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of these exercise programs as a means of fall prevention in older adults has been controversial. Some studies have demonstrated that exercise prevents falls [9][10][11][12][13][14] , but other studies have shown no effect [15][16][17] . Recently, there has been growing interest in the use of Tai Chi (TC) as an exercise for improving postural balance and prevent falling among older people [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Ou seja, existe um ciclo vicioso onde a inatividade acentua a perda funcional determinante na manutenção do equilíbrio postural e, esta perda de equilíbrio acarreta em medo de cair, que por sua vez, restringe ainda mais a atividade cotidiana do idoso. Confirmando os achados da literatura, o presente estudo mostra que a hidrocinesioterapia realizada em piscina rasa ao influenciar positivamente o controle postural e equilíbrio pode ajudar a "quebrar" este ciclo, devolvendo a funcionalidade, 275 a autonomia e a qualidade de vida aos idosos (LORD et al, 2003).…”
Section: Resultsunclassified